Effectiveness of violet LED with or without a bleaching gel: a 12-month randomized clinical trial - Lopes, Ana Cristina Távora de Albuquerque; Brondino, Nair Cristina Margarido; Bombonatti, Juliana Fraga Soares; Mondelli, Rafael Francisco Lia (Frontiers in Dental Medicine, 2024)
Introduction The present interventional, controlled, randomized, blind clinical study aimed to evaluate the effectiveness of an in-office bleaching procedure with violet LED associated or not with 37% carbamide peroxide, considering as response variables the degree of change and color stability over 12 months and dental sensitivity over a month. Methods Forty participants, according to the inclusion and exclusion criteria, were randomly divided into 2 groups (n = 20) according to the bleaching protocol conducted, in two sessions, with a 7-day interval: vLED—violet LED, without gel; vLED/CP—37% carbamide peroxide photocatalyzed with violet LED (control group). In the vLED group, in each session the bleaching was carried out by 2 consecutive irradiation cycles of 25’ each (10 × 2’ LED + 30” interval), with 5’ interval between cycles. In the vLED/CP group, the gel was applied 5 times in the bleaching session and photocatalyzed 3 times for 2’ with 30” intervals (7’30” per gel application), totaling 37’30” per session. Dental sensitivity was assessed using a visual analog scale (VAS) and the effectiveness of bleaching as a function of the degree of change and color stability (ΔE) with a spectrophotometer. The data were tabulated and submitted to statistical tests (p < 0.05). Results The VAS analysis showed that some individuals from both groups had mild pain (1 ≤ VAS < 4) during the time intervals evaluated, being more prevalent in the vLED/CP group. Regarding the degree of color change, the groups behaved differently over time (p < 0.0001). The ΔE observed for the vLED/CP group was superior in comparison to the vLED group at all evaluated moments. Conclusions Over 12 months, the vLED/CP group was more effective in relation to the bleaching effect compared to the vLED group. Both groups showed low levels of sensitivity in the studied time intervals. Clinical Trial Registration [https://ensaiosclinicos.gov.br/rg/RBR-6rc23h], identifier [U1111-1253-8850].